MENUJU LINGKUNGAN BERKELANJUTAN: PENINGKATAN PEMAHAMAN MASYARAKAT TENTANG PENTINGNYA AMDAL DALAM PEMBANGUNAN JALAN DI NEGERI HILA, MALUKU TENGAH - Murwani, Prapti; Afdhal, Afdhal (CV. Kalimasada Group, 2023)
Road infrastructure development is an important step in increasing connectivity and economic growth in an area. However, often road construction can have a negative impact on the environment if it is not managed properly. Preparing an Environmental Impact Analysis (AMDAL) is one approach that can minimize these negative impacts and maintain a balance between development and the environment. This community service aims to increase people's understanding in Hila Country, Central Maluku, about the importance of AMDAL in road construction. Through various participatory and educational activities, the service team aims to provide information about the AMDAL process, its benefits in road construction, and the importance of community involvement in environmental impact assessments. The methods used in this service involve interactive workshops, group discussions, and distribution of educational material about AMDAL. Apart from that, the service team also collaborates with related agencies to provide training to local government staff on the AMDAL process in order to improve understanding and effective implementation of AMDAL. It is hoped that the results of this service will create awareness among the community about the importance of AMDAL in road construction and their active role in making decisions regarding environmental impacts. Apart from that, it is also hoped that it can encourage broader and more comprehensive implementation of AMDAL in development projects in this area in order to achieve a sustainable environment and high carrying capacity.